Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/9434820
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Factors Influencing Telemedicine-Based Psychiatric Extended Care and Care of Psychiatric Patients

Abstract: The aim of this paper is to understand the current situation of the care burden of patients with mental illness in remission and the factors affecting it in order to provide a scientific basis for targeted interventions. This paper reviews the concept of telemedicine, the application of telemedicine in home hospice care, and the remaining problems and improvement strategies of telemedicine in home hospice care, with the aim of providing a reference for the application of telemedicine in home hospice care in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that caregivers’ negative emotions will lead to the decline of their potential coping ability and medical decision-making, which will adversely affect patients’ treatment process and disease prognosis to a considerable extent 10 11. Primary caregivers, as the most significant and frequent providers of care, are often overlooked 12 13. When a caregiver’s capacity to care fails to meet the patient’s needs, the caregiver experiences stress, leading to multidimensional burdens, including physiological, psychological and social, which are particularly pronounced during periods of surgical waiting.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that caregivers’ negative emotions will lead to the decline of their potential coping ability and medical decision-making, which will adversely affect patients’ treatment process and disease prognosis to a considerable extent 10 11. Primary caregivers, as the most significant and frequent providers of care, are often overlooked 12 13. When a caregiver’s capacity to care fails to meet the patient’s needs, the caregiver experiences stress, leading to multidimensional burdens, including physiological, psychological and social, which are particularly pronounced during periods of surgical waiting.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%